Faktor Risiko Kejadian Diare Akut pada Anak Balita (Studi Epidemiologis di Puskesmas Baamang Unit I Kabupaten Kotawaringin Timur) - Herry Poernomo; Mexitalia Setiawati; Suharyo Hadisaputro; Kamilah Budhi; Mateus Sakundarno Adi (Jurnal Epidemiologi Kesehatan Komunitas, 2016)
Background : Report from UNICEF, WHO data in 2010, there was 801.000 children aged under five was died because of diarrhea. Diarrhea cases in children aged under five in East Kotawaringin District in 3 years ago (2010-2012) increased significantly: 14,6% (2010),17,0% (2011) and 18,6% (2012), while diarrhea in 2013 decreased about 9,3%, but causing 6 deaths in children aged under five with Crude Fatality Rate (CFR) about 0,17%. Host and environment factors (age of children, exclusive breastfeeding, nutritional status, caregiver education level, caregiver knowledge level, personal hygiene, types of water facilities, types of drinking water, physical condition of latrine, chewing the food, the level of family income) are closely related to acute diarrhea. Covered: healthy house 37,32%, use of clean water facilities 65,12%, family latrine 41,3%. The purpose of this research is to explain some of hostand environment factors which is risk factors to acute diarrhea in children aged under five. Methods : This research was an observational study using case control design. Sample case are 43 children aged under five who seek treatment suffer from acute diarrhea in Public Health Centre of Baamang Unit I in East Kotawaringin District. Sample control are 43 children aged under five who seek treatment do not suffer from acute diarrhea in PublicHealth Centre of Baamang Unit I in East Kotawaringin District with consecutive sampling.Results : Age of children < 2 years (aOR=2,617; 95%CI=1,063-6,444; p=0,036); types of water facilities was not from PDAM (aOR=2,892; 95%CI=1,173-7,127; p=0,021) was risk factors to acute diarrhea with probability event together amounted was 73,6%.Conclusion : The risk factors to acute diarrhea in children aged under five was aged < 2 years and type of water facilities was not from PDAM.